Peningkatan Kemampuan Membaca Kritis Teks Berita Melalui Metode Know Want Learned (KWL) Siswa Kelas VII SMP Negeri 1 Bawolato - Delfita Hura; Noibe Halawa; Imansudi Zega; Noveri Amal Jaya Harefa (Pusat riset dan Inovasi Nasional, 2025)
Students' ability in critical reading of news texts is still lacking in understanding and analyzing the structure and language rules in news texts. This study aims to improve the ability to read critically news texts through the Know Want Learned (KWL) method in class VII-A students of SMP Negeri 1 Bawolato. The type of research used is classroom action research (CAR) using 4 stages of implementation, namely 1) planning, 2) action, 3) observation, 4) reflection. This study was carried out in 2 cycles. Based on the implementation of the study using a test to determine the structure and language rules of news texts in cycle I, the results obtained were an average value of 41.01% with the lowest value of 25 and the highest value of 75, while in cycle II there was an increase in students' critical reading ability in determining the structure and language rules of news texts with an average value obtained of 82.12%, namely the lowest value of 62.5% and the highest value of 100%. The results of this study indicate that the Know Want Learned (KWL) method can have a positive impact on improving the ability to read critically news texts. The researcher recommends that teachers at SMP Negeri 1 Bawolato can utilize the Know Want Learned (KWL) method in Indonesian language learning.